2018
DOI: 10.1177/1087724x18803116
|View full text |Cite
|
Sign up to set email alerts
|

Building Resilience Through Collaboration Between Grassroots Citizen Groups and Governments: Two Case Studies

Abstract: As sea level rise grows in importance as a public policy issue, coastal communities must search for alternative strategies to develop resilience to the growing threat. One way to tap into existing resources involves partnerships between local governments and citizen-based environmental organizations to explore strategies aimed at mitigating the effects of sea level rise and recurrent flooding in coastal communities. This article presents two cases of collaboration between governments and existing citizen group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…The vital premise of community resilience is a collaborative network in which people and organizations are connected to each other and work together. 20,21 Community disaster resilience is akin to community resilience. For highlighting the context of emergency management, the concept of community disaster resilience is used to more accurately describe a community's capacity to adapt to change, to handle disruption, and to respond in a positive and timely manner to risk or emergencies.…”
Section: Conceptualizing Community Disaster Resilience In the Public mentioning
confidence: 99%
“…The vital premise of community resilience is a collaborative network in which people and organizations are connected to each other and work together. 20,21 Community disaster resilience is akin to community resilience. For highlighting the context of emergency management, the concept of community disaster resilience is used to more accurately describe a community's capacity to adapt to change, to handle disruption, and to respond in a positive and timely manner to risk or emergencies.…”
Section: Conceptualizing Community Disaster Resilience In the Public mentioning
confidence: 99%
“…Furthermore, positive sentiment can be found for proactive strategies and the limitations of reactive ones are understood (Price, 2019). Finally, collaboration with citizen groups, other municipal governments, businesses, and research organizations can contribute to better planning (John III & Yusuf, 2019; Morris et al, 2019; Vella et al, 2016; Yusuf et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, research examining the impact of citizen participation in risk communication has confirmed that effective co-production is conditioned by open communication channels with authorities and all stakeholders in flood risk management. This can best disseminate knowledge across the community (De Boer et al, 2015;Morris, McNamara & Belcher, 2019).…”
Section: Discussionmentioning
confidence: 99%